A Pilot Clinical Study of Continuous Intravenous Ascorbate in Terminal Cancer Patients - Riordan, Hugh D.; Casciari, Joseph J.; González, Michael J.; Riordan, Neil H.; Miranda-Massari, Jorge R.; Taylor, Paul; Jackson, James A. (Puerto Rico Health Sciences Journal, 2009)
Case studies suggest that vitamin C, given intravenously at doses of 10-100 grams/day can improve patient well being and in some cases, reduce tumor size. While ascorbate is generally considered safe, clinical data on high intravenous doses is limited. Twenty-four late stage terminal cancer patients were given continuous infusions of 150 to 710 mg/kg/day for up to eight weeks. Blood chemistry and blood count profiles were obtained at roughly one-week intervals while patient health, adverse events and tumor progression were monitored. The majority of patients were vitamin C deficient prior to treatment. Intravenous infusions increased plasma ascorbate concentrations to a mean of 1.1 mM. The most common adverse events reported were nausea, edema, and dry mouth or skin; and these were generally minor. Two Grade 3 adverse events ‘possibly related’ to the agent were reported: one patient with a history of renal calculi developed a kidney stone after thirteen days of treatment and another patient experienced hypokalemia after six weeks of treatment. White blood cell counts were stable while hemoglobin and hematocrit levels dropped slightly during treatment, consistent with trends observed prior to therapy. Blood creatinine, BUN, glucose, and uric acid concentrations decreased or remained stable during therapy, suggesting that ascorbate infusions did not adversely affect renal function. One patient had stable disease and continued the treatment for forty-eight weeks. These data suggest that intravenous vitamin C therapy for cancer is relatively safe, provided the patient does not have a history of kidney stone formation.